CONSTRUCTING A STANDARDIZED TEST - SOFENDI SOFENDI (Sriwijaya University Learning and Education International Conference, 2016)
This paper is aimed at describing what a standardized test is and how it is constructed. A standardizedtest should yield good validity and reliability as well as practicality. This kind of the test is consideredas a good instrument of measurement. Constructing a standardized test requires some steps. Thesesteps lead to getting good validity, realibility, and practicality of the test. The only valid and reliabletest can be an interpretable mesurement.